Perpres No. 20/2018 dan Nasionalisme di Era Post-Truth - Puspitasari, Puspitasari (UI Scholars Hub, 2018)
This paper describes post-truth phenomena characterized by hoaxes that present in the community through social media and online media. This change of tendency is a logical consequence of the situation faced in the mass media industry and is reinforced by the tendency to strengthen politics of identity. This paper highlights how the Presidential Decree (Perpres) no. 20/2018 raises contestation that threatens national resilience through a segregation situation.